FACTORS AFFECTING LUXURY CONSUMERS ON WEBROOMING INTENTION - Intan Fauzi, Fadilah; Luki Adiati Pratomo (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2023)
The purpose of this study was to analyze the influence of perceived online search usefulness, perceived online search ease, need for touch, self-help staff, and socialization about webrooming intentions. This research uses quantitative method with Amos tool. Data collected by questionnaire technique. Respondents in this study were 251 people. The criteria for luxury goods are bags, shoes, and various products under the Kate Spade, Michael Kors and Coach brands. Five hypotheses were formulated and tested. The results showed that the perceived benefits of online search, perceived ease of online search, and self-help staff did not have a positive influence on webrooming intentions. Need for touch, and socialization have a positive influence on webrooming intentions. Thus, the company must improve information about luxury products available online is expected to be more attractive.